Efficacy and safety of Chinese herbal medicine for atopic dermatitis: Evidence from eight high-quality randomized placebo-controlled trials - Cai, Xiaoce; Sun, Xiaoying; Liu, Liu; Zhou, Yaqiong; Hong, Seokgyeong; Wang, Jiao; Chen, Jiale; Zhang, Miao; Wang, Chunxiao; Lin, Naixuan; Li, Su; Xu, Rong; et al. (Frontiers in Pharmacology, 2022)
Abstract Background: The use of Chinese herbal medicine (CHM) for the treatment of atopic dermatitis (AD) has gained attention. This quantitative study systematically evaluated the efficacy and safety of CHM for the treatment of AD in eight high-level clinical trials, resulting in a high level of clinical evidence. Methods: Several databases were searched, including PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), VIP, and Wanfang. High-quality randomized controlled trials (RCTs) comparing CHM with placebo were included. The 95% confidence interval (CI) of the risk ratio (RR) was calculated using software (RevMan 5.3) and a meta-analysis was performed. Evidence level evaluation using GRADE Profiler 3.6. Results: In total, 662 patients (322 in the experimental group and 340 in the control group) were included. The response rate of the Eczema Area and Severity Index (EASI) -90 was higher in the CHM group than in the placebo group (EASI-90: RR, 3.72; 95% CI, 1.76 to7.83; p = 0.01). Furthermore, the scoring of atopic dermatitis (SCORAD) (RR, -10.20), body surface area (BSA) (RR, -2.01), surface damage score (RR, -2.25), visual analog scale (VAS) (RR, -1.90), and sleep score (RR, -2.16), improvement of investigator’s global assessment (IGA) (RR, 2.94) improved in the CHM group. The results showed no statistical difference between CHM and placebo (MD, -0.47; 95% CI, −1.30, 0.37; p = 0.27) in improving the Dermatology Life Quality Index (DLQI) or children’s DLQI (CDLQI). There was also no significant difference in the IgE level between the two groups (MD, -62.76; 95% CI, −809.58 684.05; p = 0.87). However, the adverse events (AEs) rate was slightly higher in patients treated with CHM than in those treated with placebo (RR, 1.42; 95% CI, 1.06 to 1.90; p = 0.02). Conclusion: CHM improved the size and severity of the skin lesions and sleep quality in patients with AD. Comparing the adverse effects between the two groups, CHM is safe. However, CHM does not improve the quality of life or the patient’s IgE levels.